Role of tumor suppressor p53 and micro-RNA interplay in multiple myeloma pathogenesis - Abdi, Jahangir; Rastgoo, Nasrin; Li, Lihong; Chen, Wenming; Chang, Hong (Journal of hematology and oncology, 2017)
The molecular mechanisms underlying dysregulated wild type (wt) p53 in multiple myeloma (MM) have been subjects of intense investigation for years. Indeed, correlation of rarely occurring TP53 gene mutations or deletions with adverse clinical outcomes in MM patients is strongly established, while in majority of cases wtp53 seems to be non-functional or dysregulated bearing a high clinical impact. Interestingly, findings from recent investigations show that micro-RNAs (miRNAs) may contribute to suppression of wtp53 in MM, as they are now known to function as key regulatory elements in the p53 network. This area is shedding new light on understanding the biologic effects of dysregulated p53 in MM pathogenesis especially drug resistance. miRNAs such as miR-125b (oncomiR) or miR-34a (tumor suppressor-miR) can be negative or positive regulators of wtp53 function, respectively, with specific effects on MM cell viability. On the other hand, our knowledge of miRNA interaction with mutant (mt) p53 in MM, which is rather related to disease progression and resistance to therapy, is limited which demands in-depth exploration. Here, we will put forward the current knowledge on miRNA-p53 interaction in MM and its role in MM pathogenesis including drug resistance. We will also highlight the pre-clinical approaches for therapeutic application of miRNAs targeting p53 pathway.